Studi Pemanfaatan Kondensat Air Conditioning (AC) Menjadi Air Layak Minum - Bambang Hari P; Dia Anakorin; Tesa Manggar Retno (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2016)
Air is one of funamental resource for our life. It can be felt directly on the water work of the Air Conditioning (AC), which is currently Air Conditioning (AC) is almost installed in every office building, classroom, even in every home and the water that drains which is condensate AC thrown away. Though water from the condensate can actually be utilized as raw water may even be water unfit for consumption. By utilizing AC performance air condenses into water, where the water will be collected to be known and observed the content contained in the AC condensation process.The basis of this research is that the water from the condensate Air Conditioning can be utilized as the water unfit for consumption because of the great possibility of impurities contained in it only the impurities contained in the air. Early predictions produced water from the air conditioning process will be influenced by the place where the air conditioning was installed.The results of this study indicate that the physical parameters of the AC condensate is colorless, odorless, tasteless, TDS value of 14.27 mg / L, and Turbidity 0.77 NTU. For chemical parameters, pH value of 7.0. Further microbiological parameters indicate that the air conditioning condensate water has a value of <2 for the bacteria E-Coli and Coliform which is the smallest value from Table MPN Series 5. This indicates that the AC condensate is eligible to be used as drinking water.